Heat transfer enhancement of nanofluids in a Lid-Driven square enclosure - Rahman, M.M.; Billah, M.M.; Hasanuzzaman, M.; Saidur, Rahman; Rahim, N.A. (Numerical Heat Transfer, Part A: Applications, 2012)
A numerical investigation of mixed convection flows through a copper-water nanofluid in a lid-driven square enclosure has been executed here. The two horizontal walls of the enclosure are insulated, while the vertical walls are kept differentially heated by constant temperature with the left wall moving at a constant speed. The physical problem is represented mathematically by a set of governing equations, and the transport equations are solved using the finite element method based on Galerkin-weighted residuals. Comparisons with previously published work are performed and found to be in excellent agreement. Computational results are obtained for a wide range of parameters such as the Richardson number, solid volume fraction, and Reynolds number. Copper-water nanofluids are used with Prandtl number Pr=6.2, and solid volume fraction is varied as 0, 2, 4, and 8. Reynolds number Re is varied from 50 to 200, while the Richardson number Ri is from 0 to 5 on the flow and thermal fields; heat transfer characteristics are also studied in detail. Results are offered in terms of streamlines, isotherms, average Nusselt number, and fluid temperature for the mentioned parameters. It is found that heat transfer increased by 9.91 as increases from 0 to 8 at Ri=5. On the other hand, at the same convective regime, heat transfer increased by 120.91 as Re increased from 50 to 200.